Economic Loss of Northern Fishers Due to the Poaching Activities of Indian Trawlers - Vithursha, T.; Sivashanthini, K.; Gunaalan, K. (Vingnanam International Research Conference (VIRC), 2018)
The present study was carried out to analyze the economic loss of Sri Lankan fishers due to the poaching activities by Indian trawlers. Fishery resources are major livelihoods in South Indian and North Sri Lankan people who have been fished in harmony since ancient time but the situation has gone upside down since early 90s. Because fish stocks on the Indian side were fast depleting due to over-exploitation, the number of Indian fishing vessels entering into Sri Lankan waters for fishing also rapidly increased. A survey was carried out at Karainagar, Point Pedro and Mathagal region from September 2015 to February 2016 in order to assess the economic loss of Sri Lankan fishers from indicated areas. Primary data related to yield lost, income lost and nautical lost were collected from 100 families by providing a pre-tested questionnaire and secondary data related to the economic lost were collected from co-operative societies of the respective regions. Collected data were subjected to descriptive statistical analysis and one-way analysis of variance. The highest yield lost was recorded in Point Pedro followed by Mathagal, which were being 435.20 ± 125.8 kg/month and 428.10 ± 120.0 kg/month respectively. Mathagal area faced significantly (P < 0.05) high amount of income lost (SLR/month 85, 571.00 ± 35,119.00) than the other area. The nautical lost in Karainagar, Point Pedro and Mathagal area were 8, 6 and 5 Nautical Miles respectively. Fishers living in Mathagal and Point Pedro area faced significantly (P < 0.05) high amount of economic lost by Indian trawlers than the Karainagar area. From the present study it can be concluded that the intrusion of Indian trawlers into the Sri Lankan territorial waters should be restricted in order to reduce the economic loss of the Sri Lankan fishers.
Keywords: Economic loss; Invasion; Poaching; Territorial